2012
DOI: 10.3988/jcn.2012.8.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Medial Temporal Atrophy and Memory Dysfunction in Poststroke Cognitive Impairment-No Dementia

Abstract: Background and PurposeIt was recently reported that the prevalence of poststroke memory dysfunction might be higher than previously thought. Stroke may exist concomitantly with underlying Alzheimer's disease (AD), and so we determined whether post-stroke memory dysfunction indicates manifestation of underlying subclinical AD.MethodsOf 1201 patients in a prospective cognitive assessment database, we enrolled subjects with poststroke amnestic vascular cognitive impairment-no dementia (aVCIND; n=48), poststroke n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…This amnestic VCI conceivably might represent a mixed type pre‐manifest dementia with additional pathology of AD. Whilst this remains speculative without evidence for amyloid pathology using CSF or positron emission tomography (PET)‐imaging, our findings are well in line with a previous report of less severe MTA scores in non‐amnestic post‐stroke VCI compared with amnestic subtypes .…”
Section: Discussionsupporting
confidence: 90%
“…This amnestic VCI conceivably might represent a mixed type pre‐manifest dementia with additional pathology of AD. Whilst this remains speculative without evidence for amyloid pathology using CSF or positron emission tomography (PET)‐imaging, our findings are well in line with a previous report of less severe MTA scores in non‐amnestic post‐stroke VCI compared with amnestic subtypes .…”
Section: Discussionsupporting
confidence: 90%
“…In addition, stroke-mediated cognitive deficits are more strongly associated with lesions that affect the dominant hemisphere (Kalaria et al, 2016). The risk factors for post-stroke dementia are multifactorial, and include advanced age, genetic traits, low educational status, stroke severity, presence of diabetes, multiple infarcts, prior transient ischemic attack or recurrent stroke, and depressive illness (Gregoire et al, 2012; Jacquin et al, 2012; Kalaria et al, 2016; Kim et al, 2012; Leys et al, 2005; Lin et al, 2003; Yang et al, 2015). …”
Section: Age-related Vcidmentioning
confidence: 99%
“…Few studies have been conducted on the MVCI incidence rate in Korea. Only one study reported an incidence rate of 39.0% (n ¼ 156) for mild cognitive impairment among 396 Korean stroke patients [8].…”
Section: Introductionmentioning
confidence: 99%